Studiehandledning på modersmål: Studiehandledares positionering och yrkesroll - Rosén, Jenny; Straszer, Boglarka; Wedin, Åsa (Educare, 2019)
In this article focus is directed towards Study Guidance in the Mother Tongue (SGMT) and SGMT tutors’ professional roles in Swedish compulsory school. The aim is to study how SGMT tutors are positioned and position themselves in relation to official documents and other actors in school. Questions that are illuminated in the article deal with forms for participation in school activities, opportunities to agency and voice as well as expressions of professionality in the SGMT tutor role. The empirical material consists mainly of interviews with SGMT tutors together with official documents. The results show that there is considerable variation between individual SGMT tutors when it comes to their opportunities for agency, making their voices heard, participation and influence. Several co-operating factors have been identified that may strengthen the SGMT tutors’ profession: own competence, co-operation with class and subject teachers and organisational concerns (for example, time allocated for preparation).